Endometrial thickness and early pregnancy complications after frozen-thawed embryo transfers - Song, Lin; Bu, Zhiqin; Sun, Yingpu (Frontiers in Endocrinology, 2023)
Background: The relationship between endometrial thickness and pregnancy safety after in vitro fertilization treatment is an important topic that should provoke attention. The aim of this study was to demonstrate the relationship between endometrial thickness on day of embryo transfer and early pregnancy complications, including ectopic pregnancy and early miscarriage, in frozen thawed embryo transfer (FET) cycles. Methods: Patients undergoing their first FET cycles were included into this study from January 2010 to December 2021. Patients were divided into three groups according to endometrial thickness on day of embryo transfer: Thin, ≤ 7 mm; Medium, 7-14 mm; Thick, ≥ 14 mm. Ectopic pregnancy and early miscarriage were the two primary outcomes. Endometrial thickness was the main measured variable. The risk factors of these two compilations were determined based on univariate analysis and multivariate logistic regression analysis. Results: A total of 11138 clinical pregnancies were included. The overall ectopic pregnancy and early spontaneous miscarriage rates were 2.62% and 13.40%. The ectopic pregnancy and early spontaneous miscarriage rates were significantly higher in patients with thin endometrium as compared with those in the other two groups (ectopic pregnancy rate: 5.06% vs. 2.62% vs. 1.05%; P < 0.001; early spontaneous miscarriage rate: 15.18% vs. 13.45% vs. 11.53%; P < 0.001). In multivariate logistic regression analysis, thin endometrium was an independent factor to predict ectopic pregnancy [adjusted odds ratio (aOR): 5.62; 95% confidence interval (CI): 2.51–12.58, P < 0.001], and to predict early spontaneous miscarriage rate (aOR: 1.57; 95% CI: 1.21–1.74, P < 0.001). Conclusions: Thin endometrium on day of embryo transfer in FET cycles is an independent predictor for early pregnancy compilations, including ectopic pregnancy and early spontaneous miscarriage.